Estimating organic aerosol emissions from cooking in winter over the Pearl River Delta region, China. (1st January 2022) - Xing, Li; Fu, Tzung-May; Liu, Tengyu; Qin, Yiming; Zhou, Liyuan; Chan, Chak K.; Guo, Hai; Yao, Dawen; Duan, Keqin
Abstract: Cooking is an important source of organic aerosols (OA), particularly in urban areas, but it has not been explicitly included in current emission inventories in China. This study estimated the organic aerosol emissions from cooking during winter over the Pearl River Delta (PRD) region, China. Using the retrieved hourly cooking organic aerosol (COA) concentrations at two sites in Hong Kong and Guangzhou, population density, and daily per capita COA emissions, we determined the spatial and temporal distribution of COA emissions over the PRD region based on two approaches by treating COA as non-volatile (NVCOA) and semi-volatile (SVCOA), respectively. By using the estimated COA emissions and the Weather Research and Forecasting model coupled with chemistry (WRF-Chem) model, we reproduced the diurnal cycles of COA concentrations at the PolyU site in Hong Kong and Panyu site in Guangzhou. We also resolved the different patterns of COA between weekdays and weekends. The mean COA concentration during wintertime over the urban areas of the PRD region was 0.7 μg m −3 and 0.9 μg m −3 for the NVCOA and SVCOA cases, respectively, contributing 5.1% and 6.9% to the urban OA concentrations. The total COA emissions in winter over the PRD region were estimated to be 3.5 × 10 8  g month −1 and 3.8 × 10 8  g month −1 for the NVCOA and SVCOA cases, respectively, adding 34.8% and 37.8% to the total primary organic aerosol emissions. Considering COA emissions in the model increased the mean regional OA concentrations by 4.6% and 7.4% for the NVCOA and SVCOA cases, respectively. Our study therefore highlights the importance of cooking activities to OA concentrations in winter over the PRD region. Highlights: Cooking organic aerosol (COA) emissions were (3.5–3.8)×10 8 g month -1 in winter. COA emissions added 34.8%–37.8% to the primary organic aerosol (OA) emissions. COA contributes 5.1%–6.9% to OA concentrations over the urban areas. COA emissions increased OA concentrations by 4.6%–7.4%.